Maternal immunity and African swine fever virus: understanding the limits of passive protection - Friedrichs, Virginia; Streitz, Mathias; Beer, Martin; Blome, Sandra; Schäfer, Alexander (Frontiers in Immunology, 2025)
African swine fever (ASF) is an often-fatal disease impacting domestic and wild pigs world-wide. Understanding the role of maternal immunity in ASF pathogenesis is crucial for effective control. This study characterized kinetics and protective potential of maternal immunity against ASF virus (ASFV) in neonatal piglets. Two times ten sows were inoculated with the moderately virulent ASFV strain ‘Estonia2014’, all developed typical ASF signs and viraemia; five animals recovered. The offspring of two recovered sows (n = 24) were sampled weekly to monitor maternal ASFV-specific antibody kinetics. The offspring of two other sows, in addition to piglets of an ASFV-naïve sow, were challenged oro-nasally with the highly virulent ASFV strain ‘Armenia2008’ on the seventh day of life. To evaluate the impact of ASFV-specific antibodies without ASFV-specific T cells, five piglets from the naïve sow received purified, concentrated immunoglobulins from ASFV-immune pigs via serum transfer prior to challenge infection. All naïve piglets (n = 12), regardless of immunoglobulin transfer, reached the humane endpoint 6 days post inoculation (dpi). Piglets of immune sows began displaying clinical signs 5 dpi, and all either succumbed or reached the humane endpoint by 9 dpi (n = 27). Serology confirmed antibodies against ASFV (p32, p72) in all piglets of immune sows. Antibody titers in unchallenged piglets remained stable for at least 60 days after birth. In challenged piglets, those of immune sows were initially seropositive but mostly seronegative after challenge, indicating antibody consumption. Passively transferred antibodies were also depleted after challenge. In conclusion, passively acquired immunity, whether through immunoglobulin transfer (antibodies) or colostrum (antibodies and lymphocytes), is insufficient to safeguard neonatal pigs from lethal infection with highly virulent ASFV.